The language of sycamores - Wingate, Lisa (New York : Berkley, 2019)
After Karen Sommerfield is suddenly forced to deal with the threat of cancer at the same time her company downsizes her, she returns to the rural Missouri Ozarks and her grandmother's old farm on an odyssey to find herself.
Keywords: Downsizing of organizations -- Fiction; Loss (Psychology) -- Fiction; Cancer in women -- Fiction; Married women -- Fiction; Unemployed -- Fiction; Farm life -- Fiction; Children -- Fiction; Sisters -- Fiction; Cancer in women; Children; Downsizing of organizations; Farm life; Loss (Psychology); Married women; Sisters; Unemployed; Ozark Mountains -- Fiction; Missouri -- Fiction; Missouri; United States -- Ozark Mountains; Psychological fiction; Domestic fiction; Domestic fiction; Fiction; Psychological fiction